Implementasi Metode Clustering Algoritma K-Means untuk Menentukan Kelompok Tahfidz dan Tahsin di Pesantren Siswa Al-Ma’soem - Sofia Dewi; Siti Fatimah (Jurnal Accounting Information System (AIMS), 2023)
Determining the tahfidz and tahsin groups with computer programs is an effort that needs to be done to find out the ability of students during this tahfidz program. At this time, in the process of grouping tahfidz and tahsin at pesantren Siswa Al Ma'soem, it is necessary to Cluster with data so that the ability of students in answering the test can be known the student's self-limit and enter the tahfidz or tahsin group. In this study, 349 data were used as the main data for clustering using the K-Means algorithm with tests carried out on Rapidminer and Microsoft Excel. Based on the results of the analysis in the research conducted, it can be concluded that from 4 attributes. In Cluster 1 with a total of 177 students, it was declared into the tahfidz group. In addition, other cluster with a total of 172 students who entered the tahsin group with validation of 0.312 and 0.238 in Microsoft Excel and Rapidminer which stated that the smaller the validation number, the better the cluster used.